2004
DOI: 10.1021/ac049324m
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Polar Drug Residues in Sewage and Surface Water Applying Liquid Chromatography−Tandem Mass Spectrometry

Abstract: A simple and rapid method is presented for the trace-level analysis of 10 polar pharmaceutical residues in various types of water samples from the aquatic environment. Using this method, the pharmaceuticals and several drug metabolites can be analyzed in drinking and surface waters and in wastewater (treated and untreated sewage) at concentrations down to 0.01 microg/L. Samples are prepared by a simple in situ derivatization enabling the preconcentration of very polar metabolites by automated solid-phase extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…They also showed that the composition of the eluent influences the signal response in ESI more strongly than in APCI and that adduct formation may be stronger in ESI. These latter two findings are in agreement with observations from real samples that the analyte response in APCI has been found to be less affected by coeluting matrix components than in ESI [202][203][204][205]. These are some arguments in favor of APCI.…”
Section: 52supporting
confidence: 91%
“…They also showed that the composition of the eluent influences the signal response in ESI more strongly than in APCI and that adduct formation may be stronger in ESI. These latter two findings are in agreement with observations from real samples that the analyte response in APCI has been found to be less affected by coeluting matrix components than in ESI [202][203][204][205]. These are some arguments in favor of APCI.…”
Section: 52supporting
confidence: 91%
“…1, indicate that a very good liquid-phase separation efficiency was obtained. Additionally, since most studies have demonstrated that APCI is less matrix sensitive that ESI (Chen et al, 2014;Zuehlke et al, 2004), MS/MS parameters were also optimized for APCI. However, APCI was discarded for further determinations due to the lower instrumental response to both analytes and the narrow linear range especially for PAA (data not shown).…”
Section: Optimization Of Ms/ms Conditionsmentioning
confidence: 99%
“…CBZ also presents an interesting anthropogenic marker for the water cycle. The CBZ concentration in water samples can be determined by chromatographic methods such as liquid chromatographytandem mass spectrometry (LC-MS/MS) 12 or immunochemical methods. 13,14 Only recently a direct competitive enzyme immunoassay (EIA) using the enzyme horseradish peroxidase (HRP) and the chromogenic substrate 3,3 …”
mentioning
confidence: 99%